Effectiveness of Pelvic Rocking Exercise on Primary Dysmenorrhea among Midwifery Students - Dina Raidanti; Wahidin Wahidin; Siti Fathimah; Christin Jayanti (Jurnal Bidan Cerdas, 2025)
Background: Primary dysmenorrhea is one of the most common gynecological problems experienced by women of reproductive age, characterized by spasmodic cramps and lower abdominal pain without pathological abnormalities. This condition negatively affects academic activities, productivity, and quality of life. Pelvic rocking exercise, a simple movement using a gym ball, has been suggested to improve uterine blood flow, reduce uterine muscle contractions, and stimulate endorphin release to decrease pain intensity. This study aimed to evaluate the effectiveness of pelvic rocking exercise on primary dysmenorrhea among undergraduate midwifery students. Methods: A quasi-experimental study with a one-group pretest–posttest design was conducted involving 18 first-year midwifery students experiencing primary dysmenorrhea, selected using accidental sampling. Pain intensity was measured before and after a 15-minute pelvic rocking exercise session and analyzed using the Wilcoxon signed-rank test. Results: The mean pain intensity before the intervention was 5.77 (moderate category), which decreased to 2.44 (mild category) after the intervention. The Wilcoxon test showed a p-value = 0.000 (p < 0.05), indicating a significant reduction in pain intensity. Conclusion: Pelvic rocking exercise was proven effective in reducing primary dysmenorrhea among midwifery students. It can therefore be recommended as a non-pharmacological intervention in managing menstrual pain.